Binomial Assignment
Binomial Assignment
Binomial Assignment
BINOMIAL THEOREY
1. Expand:
(i) (1 − x + x 2 ) in powers of x
4
(ii) (1 + x + x 2 ) in powers of x
3
( ) ( )
6 6
x +1 + x −1 + x +1 − x −1
2. Evaluate:
9
4x 5
3. (i) Find the 7 term in the expansion of −
th
5 2x
12
x 3a
(ii) Find the 9 term in the expansion of − 2
th
a x
(iii) Find ‘a’ if the 17th and 18th terms of the expansion ( 2 + a ) are equal.
50
i. x 5 in the expansion of ( x + 3)
6
11
3
10
ii. x in the expansion of 2 x 2 − , x 0
x
11 11
1 1
5. Find the coefficient of x in ax 2 + and that of x −7 in ax − 2 and then find the relation
7
bx bx
between a and b so that these coefficients are equal, none of a, b and x is zero.
1024
12 1
6. Find the number of integral terms in the expansion of 5 + 7 8
(a) 102 (b) 124 (c) 158 (d) 129
Expand (1 + x )
n +1
8. , when x = 8. Deduce that 9n +1 − 8n − 9 is divisible by 64 for all n N
BINOMIAL 2
( )
20
14. Let R = 8 + 3 7 then prove that
Answers Key
1. (i) 1 − 4 x + 10 x 2 − 16 x3 + 19 x 4 − 16 x5 + 10 x 6 − 4 x 7 + x8 (ii) 1 + 3x + 6 x 2 + 7 x3 + 6 x 4 + 3x5 + x 6
a4
2. 16 x (14 x − 3)
10500
C4 .3 . 12 , 1, n Cr −1 ( x ) .a n − r +1
2 12 8 r −1
3. ,
x3 x
4. 18, 28.35.55 , 29568 5. ab = 1 6. d 7. -43, -6
10. 8 11. 1 12. 001 13. b 15. b
Solutions
1. Expand:
(i) (1 − x + x 2 ) in powers of x
4
(ii) (1 + x + x 2 ) in powers of x
3
(
(i) (1 − x + x 2 ) = (1 + x 2 ) − ( x ) )
4 4
Sol:
= (1 + x 4 + 2 x 2 ) − 4 x (1 + x 6 + 3x 2 + 3x 4 ) + 6 x 2 (1 + x 4 + 2 x 2 ) − 4 x3 (1 + x 2 ) + x 4
2
= 1 − 4 x + 10 x 2 − 16 x3 + 19 x 4 − 16 x5 + 10 x 6 − 4 x 7 + x8
(ii) (1 + x + x 2 ) = ( (1 + x ) + x 2 )
3 3
= (1 + x3 + 3x + 3x 2 ) + 3x 2 (1 + x 2 + 2 x ) + 3 x 4 (1 + x ) + x 6
= 1 + 3x + 6 x 2 + 7 x3 + 6 x 4 + 3x5 + x 6
( ) ( )
6 6
x +1 + x −1 + x +1 − x −1
2. Evaluate:
Sol: Here,
( ) ( ) ( )( ) ( ) ... (1)
6 6 5 1 6
x + 1 + x −1 = 6C0 x + 1 + 6C1 x +1 x − 1 + .... + 6C6 x −1
( ) ( ) ( )( ) ( ) ..... ( 2 )
6 6 5 1 6
x +1 − x −1 =6 C0 x + 1 − 6C1 x +1 x − 1 + .... + 6C6 x −1
( ) ( )
6 6
x +1 + x −1 + x +1 − x −1
(iii) Find ‘a’ if the 17th and 18th terms of the expansion ( 2 + a ) are equal.
50
9
4x 5
Sol: (i) Given, −
5 2x
9−k
−5
k
4x
General term Tk +1 = 9Ck
5 2x
For 7th term, putting k = 6
4 x −5
3 6
T7 = 9C6
5 2x
10500
=
x3
12
x 3a
(ii) Given, − 2
a x
12 − k
−3a
k
x
General term Tk +1 = Ck
12
2
a x
For 9th term, putting k = 8
x −3a
4 8
T9 = C8 2
12
a x
a4
= 12C4 .38. 12
x
BINOMIAL 5
(iii) Given, ( 2 + a )
50
(iv) Given, ( x + a )
n
Tn − r + 2 = T( n − r +1)+1
= nCn − r +1 ( x ) (a)
n − n + r −1 n − r +1
= nCr −1 ( x )
r −1
.a n − r +1
i. x 5 in the expansion of ( x + 3)
6
11
3
ii. x 10
in the expansion of 2 x 2 − , x 0
x
( x + 3)
6
Sol: (i) Given,
For coefficient of x 5
6−k =5
k =1
⸫ Coefficient of x 5 is
= 6C1.31
= 18
BINOMIAL 6
11
3
(ii) Given, 2x 2 −
x
−3
k
Tk +1 = Ck ( 2 x
11
)
2 11− k
x
= 11Ck .211− k .x 22−2 k . ( −3) .x − k
k
= 28.35.55
(iii) Given, ( x 2 − 2 )
11
Tk +1 = 11Ck ( x 2 )
11− k
( −2 )
k
= 11Ck ( −2 ) x 22−2 k
k
= 11C6 ( −2 )
6
= 29568
11 11
1 1
5. Find the coefficient of x 7 in ax 2 + and that of x −7 in ax − 2 and then find the relation
bx bx
between a and b so that these coefficients are equal, none of a, b and x is zero.
11 k
1 11− k 1
Sol: For ax 2 + , Tk +1 = 11Ck ( ax 2 )
bx bx
1 22−3k
= 11Cr a11− k x
bk
BINOMIAL 7
For x7 , 22 − 3k = 7
3k = 15
k =5
1
T6 = 11C5 a 6 5 x 7
b
11
1 a5
Similarly, coefficient of x −7
in ax − 2 is C6 6
11
bx b
a 6 11 a5
Given that 11 C5 = C6 6
b5 b
1
a=
b
or ab = 1
1024
12 1
6. Find the number of integral terms in the expansion of 5 + 7 8
(a) 102 (b) 124 (c) 158 (d) 129
Ans: (d)
1024
1 1
Sol: Given, 5 2 + 7 8
Tk +1 = 1024Ck ( 51/2 ) (7 )
1024 − k 1/8 k
1024 − k k
= 1024Ck 5 2
78
Here, for integral terms
1024 − k k
and both have to be integer.
2 2
Thus,
k = 0,8,16, 24,....1024
Thus total 129 terms
(i) Given, (1 + 2 x ) (1 − x )
6 7
Sol:
BINOMIAL 8
(1 + 2 x ) (1 − x )
6 7
= ( C + C ( 2x ) + C ( 2x )
6
0
6
1
1 6
2
2
+ ... )( C − C x + C x
7
0
7
1
7
2
2
+ ...)
= 6C3 ( 2 ) . 7C0 + 6C2 ( 2 ) . 7C1 ( −1) + 6C1 ( 2 ) . 7C2 ( −1) + 6C6 . 7C3 ( −1)
3 2 1 1 2 3
(ii) Given, (1 + x ) (1 − x )
3 6
= 3C3 . 6C2 ( −1) + 3C2 .6 C3 ( −1) + 3C1.6 C4 ( −1) + 3C0 . 6C5 ( −1)
2 3 4 5
= 15 − 60 + 45 − 6
= −6
Expand (1 + x )
n +1
8. , when x = 8. Deduce that 9n +1 − 8n − 9 is divisible by 64 for all n N
Given, (1 + x )
n +1
Sol:
(1 + x )
n +1
= n +1C0 + n +1C1 x + n +1C2 x 2 + .... + n +1Cn +1 x n +1
Putting x = 8, we get
9n +1 = n +1C0 + n +1C1.8 + n +1C2 .82 + .... + n +1Cn +1 8( n +1)
9n +1 = 1 + 8 ( n + 1) + 82 ( n +1
C2 + n +1C3 8 + .... + n +1Cn +1 8(
n −1)
)
9n +1 − 8n − 9 = 64 ( Integer )
or (1 + 3) − 3n − 1
n
(ii) Given, 32 n + 2 − 8n − 9
or ( 32 )
n +1
− 8n − 9
(9)
n +1
− 8n − 9
(1 + 8 )
n +1
− 8n − 9
( x − y + y ) − yn
n
( C ( x − y)
n
0
n
+ nC1 ( x − y )
n −1
y1 + nC2 ( x − y )
n−2
y 2 + .... + nCn −1 ( x − y ) y n −1 + nCn y n − y n )
( x − y ) n C0 ( x − y ) + nC1 ( x − y ) y + ... + nCn −1 y n −1
n −1 n−2
( x − y ) Integer for all n N
( x + y − y)
2 n +1
+ y 2 n +1
( 2 n +1
C0 ( x + y )
2 n +1
− 2 n +1C1 ( x + y ) . y + 2 n +1C2 ( x + y )
2n 2 n −1
y 2 + .... + 2 n +1C2 n ( x + y ) . y 2 n − 2 n +1C2 n +1 y 2 n +1 )
+ y 2 n +1
BINOMIAL 10
Hence proved
10. Find remainder when 599 is divided by 13.
Sol: Given, 599
599 = 5.598
= 5 ( 52 )
49
= 5 ( 26 − 1)
49
9100 = (1 + 8 )
100
Given, ( 29 )
100
Sol:
( 29 ) = ( 30 − 1)
100 100
= 100C0 30100 − 100C1 3099 + 100C2 3098 − .... + 100C98 ( 30 ) − 100C99 ( 30 ) + 100C100
2
Ans: (b)
Sol: Given, 181808 − 81808 + 111008
( )
20
14. Let R = 8 + 3 7 then prove that
( )
20
Sol: Given, R = 8 + 3 7
( ) ( 0 G 1)
20
Let G = 8 − 3 7
Now,
( ) ( ) + .....
1 2
R = 20C80 820 + 20C1 819 3 7 + 20C2 818 3 7
(3 7 ) + (3 7 ) + ...
1 2
G = 20C0 820 − 20C1 819 20
C2 818
R + R + G = 2 ( k ) ( k isinteger )
Since 0 G 1 & 0 R 1
0 G + R 2
G + R = 1
R = 2k − 1 ( odd )
Also, ( R )( G ) = 1
BINOMIAL 12
G + R = 1
R = 1 − G
1
R = 1 −
R
1
R = 1 −
(8 + 3 7 )
20
Given, (1 + x )
50
Sol: